Pengaruh Alokasi Belanja Operasi dan Belanja Modal pada Indeks Pembangunan Manusia - Sasti, Ida Ayu Tari Purnama; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 26 No 2 (2019)DO - 10.24843/EJA.2019.v26.i02.p29, 2019)
This study aims to obtain empirical evidence regarding the effect of operating expenditure and capital expenditure allocation on the human development index. This research was conducted in 9 regencies / cities in the province of Bali. The population in this study is the entire Report on Realization of Regional Revenues and Expenditures and the Human Development Index of all Regency / City of the Province of Bali in 2013-2017. The method of determining the sample used is a saturated sample, with a total sample of 45 observations. The data analysis technique used is multiple linear regression analysis. Based on the results of the study indicate that operating expenditure has an effect on the human development index and capital expenditure has no effect on the human development index. Keywords : Operating expenditure, capital expenditure, human development index